La morale sexuelle, la famille et les droits reproductifs vus par le réseau transnational des femmes communistes dans les années 1920 - Daria Dyakonova (Cahiers d’histoire.)
The international communist women’s movement founded in 1920 fought for the full political, economic and social equality between men and women which was to be achieved through the revolutionary transformation of the capitalist system. It also aspired to create a society based on a new morality. The bourgeois family had to give way to a proletarian unit where two individuals would be free and independent. The movement urged to grant women freedom of choice in matters of reproduction where moral judgment would no longer play a primary role. Prostitution was also seen as a social phenomenon linked to the economic inequality of sexes present in a capitalist system and not as a sin. In contrast, the discourse on sexual freedom was quite complex. Supported by the youth of the Soviet Komsomol, sexual liberation was, however, viewed with caution (and sometimes suspicion) by some communist women.